Development of Cellular Therapeutics for Cancer Treatment: Functional Enhancements Without Genetic Modification - Harada, Yui (Drug Delivery System, 2025)
The treatment landscape for malignant tumors, particularly solid tumors, has undergone profound shifts with the emergence and development of molecularly targeted therapies and advanced immunotherapeutic agents. These innovative approaches have contributed to steadily improving therapeutic outcomes, and in many cases, early detection paired with prompt intervention has enabled curative treatment. However, malignant tumors remain the leading cause of mortality in Japan - a reflection of the limited success in treating certain cancer types despite advances in technology and therapeutics. At the forefront of therapeutic technology development, significant efforts are being devoted to enhancing the functionality of cell-based therapeutics. This article focuses particularly on surface modifications applied to cells without genetic modifications. We hope it will contribute to a deeper understanding of the mechanisms of action and therapeutic strategies of newly emerging agents, while also strengthening the momentum toward the eradication of cancer.